Association between allergen-specific immunoglobulin E sensitization, allergic rhinitis symptoms, and quality of life in school-aged children - Daisuke Watanabe; Sanae Otawa; Megumi Kushima; Hideki Yui; Ryoji Shinohara; Zentaro Yamagata; Daiju Sakurai; Kunio Miyake; The Yamanashi Adjunct Study of the Japan Environment and Children’s Study Group (Scientific Reports)
Abstract This study aimed to investigate the relationship between allergen-specific immunoglobulin E (IgE) sensitization and allergic rhinitis (AR) symptoms in school-aged children in Japan and to understand the current severity of AR symptoms and the quality of life (QOL) among children with AR. We analyzed data from 8-year-old children who participated in the Yamanashi Adjunct Study of the Japan Environment and Children’s Study, focusing on those with complete information on specific IgE levels and AR (1229 for perennial AR [PAR] and 1196 for seasonal AR [SAR]). Sensitization was determined when allergen-specific IgE levels were class 2 (0.70 U/mL) or higher. A total of 656 children (53.4%) were identified as sensitized to house dust mite-specific IgE, comprising 362 (60.6%) boys and 294 (46.5%) girls. For Japanese cedar pollen (JCP)-specific IgE, 820 (68.6%) children were sensitized, with 430 (73.1%) boys and 390 (64.1%) girls. Among children with AR, 40.2% of those with PAR and 78.4% of those with SAR experienced moderate to severe nasal symptoms. This study highlighted the high prevalence of JCP-specific IgE sensitization among school-aged children in Japan and provided insights into the severity of AR symptoms and the impact on QOL in these children.